Web standards mastering HTML5, CSS3, and XML - Sikos, Leslie F.; SpringerLink (Online Service). (Berkeley, CA Apress, 2011)
Web standards: mastering HTML5, CSS3, and XML provides solutions to the most common website problems, and gives you a deep understanding of web standards and how they can be applied to improve your website. You will learn how to create fully standards-compliant websites and provide search engine-optimized Web documents with faster download times, accurate rendering, correct appearance and layout, lower development cost, approved accessibility, backward and forward compatibility, and easy maintenance and content updating. The book covers all major Web standards, focusing on syntax, grammar, recommended annotations, and other standardization concerns. Web Standards: Mastering HTML5, CSS3, and XML is also a comprehensive guide to current and future standards for the World Wide Web. As a web developer, you'll have seen problems with inconsistent appearance and behavior of the same site in different browsers. Web standards can and should be used to completely eliminate these problems. Web Standards: Mastering HTML5, CSS3, and XML describes how you can make the most of web standards, through technology discussions as well as practical sample code that you can use for your own sites and web applications. It also provides a quick guide to standard website creation for Web developers.
Electronic reproduction.
Keywords: Web sites -- Design; HTML (Document markup language).; XML (Document markup language).; Cascading style sheets; Electronic books